essentials of bussines process outsourching - Thomas N. Duening, Rick L. Click (John Wiley & Sons, Inc., 2005)
Business process outsourcing (BPO) has emerged as one of the leading business and economic issues of our time.A natural extension of the free-trade movement that has been a dominant force in global economics over the past two decades, BPO has been met with mixed reactions.Workers whose lives have been disrupted because their jobs have been outsourced to lower-wage workers overseas have understandably decried â€œoffshoringâ€ as a threat to their way of life. Others, especially those in the foreign locations where new jobs are rapidly being created, are elated finally to have an opportunity to gainfully deploy their hard-earned skill sets.